Method for recovering ammonium perrhenate from crystallization tail liquid
Through a series of pretreatment, impurity removal and crystallization steps, the problem that the purity and rhenium recovery rate of ammonium perrhenate product in the prior art is difficult to improve simultaneously, and a high purity and high recovery rate of ammonium perrhenate product is achieved.
Patent Information
- Application Number
- CN202411538901.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to meet the requirements of purity of ammonium perrhenate product and rhenium recovery rate, resulting in low product purity and waste of rhenium resources.
By oxidation and quicklime neutralization pretreatment, nano-level impurity removal and filter cloth removal, ion exchange resin adsorption and impurity removal, nano-level impurity removal of desorption liquid, cross-flow filtered clear liquid concentration and ultrasonic assisted crystallization, and finally washing and Dry and recover ammonium perrhenate.
It improves the purity of ammonium perrhenate products and the comprehensive recycling rate of rhenium elements, reduces resource waste, and ensures high quality of products.
Smart Images

Figure CN119430293A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical production, relates to ammonium perrhenate, and specifically relates to a method for recovering ammonium perrhenate from crystal tail liquid. Background Art
[0002] Rhenium is a rare metal element with a high melting point, which is often used in the aerospace field. Since rhenium is an indispensable element in the preparation process of aircraft engine turbofans and steam turbine turbofans, it is considered a strategic element. Rhenium is oxidized into high-valent oxides during the molybdenum smelting process, and then sublimates into the smelting flue gas. In the spray system before the flue gas acid production, it is enriched in the eluent. The cooling crystallization process is mainly used to recover ammonium perrhenate from the rhenium-containing eluent in the product stage, and a large amount of high-impurity crystallization tail liquid will inevitably be produced in the production.
[0003] The crystal tail liquid generated in the rhenium recovery production has a high rhenium concentration, but also contains high impurity elements. After analyzing the crystal tail liquid, the rhenium content is 2-3 g / L, the impurity elements molybdenum, sulfur and fluorine content is also between 2-6 g / L, and the impurity elements fluorine, sulfur and tungsten are about 55-60 mg / L, mainly in the form of sulfate ions, sulfite ions, molybdate ions, fluoride ions and silicate ions. The treatment method of the prior art has the following deficiencies:
[0004] First, the crystal tail liquid is diluted and returned to the original ion exchange adsorption system. Since the impurities in the crystal tail liquid are too large, the quality of the existing ammonium perrhenate product will be greatly reduced, and the addition of ammonia water will cause the adsorption efficiency of the existing resin to decrease.
[0005] Second, the crystal tail liquid is directly concentrated, crystallized and evaporated to form the product ammonium perrhenate. The obtained ammonium perrhenate product has a large amount of impurities and the purity of the finished product is 40-60%.
[0006] Third, the crystallization tail liquid is pre-treated by neutralization with quicklime to reduce impurities before concentrated crystallization. The rhenium element is lost in a large amount and the purity of the ammonium perrhenate product is not high.
[0007] Fourth, the method of diluting the crystal tail liquid and then performing ion exchange adsorption is adopted. The ion exchange resin is easily saturated due to the high impurity content of the adsorption liquid, and the purity of the produced ammonium perrhenate product is not high.
[0008] Fifth, the crystallization tailings are directly added to the molybdenum concentrate roasting system for secondary roasting to allow the rhenium element to be oxidized and overflowed again. Due to the many circulation links in this method, the final rhenium metal recovery rate is estimated to be less than 15%, resulting in a large amount of resource waste. Summary of the invention
[0009] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for recovering ammonium perrhenate from crystallization tail liquid, so as to solve the technical problem that it is difficult to simultaneously meet the requirements of the purity of the ammonium perrhenate product and the recovery rate of the rhenium element in the prior art.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0011] A method for recovering ammonium perrhenate from a crystallization tail liquid, the method comprising the following steps:
[0012] Step 1: Oxidation and quicklime neutralization pretreatment:
[0013] To the crystal tail liquid containing impurities to be treated, hydrogen peroxide with a concentration of 25-30wt.% and ammonia water with a concentration of 25-28wt.% are added in sequence to obtain the crystal tail liquid containing treated impurities.
[0014] The crystal tail liquid containing the treated impurities is stirred and heated, and quicklime is added to the crystal tail liquid containing the treated impurities to obtain the pretreated crystal tail liquid.
[0015] Step 2: Nano-scale impurity removal and filter cloth impurity removal:
[0016] Under the condition of 75-85° C., the pretreated crystallization tail liquid obtained in step 1 is filtered by cross-flow filtration with a filter element of 100 nm, and the concentrated liquid after filtration is returned to the original liquid tank for secondary utilization.
[0017] After the temperature of the filtered clear liquid drops to room temperature, the insoluble impurities precipitated during the cooling process of the filtered clear liquid are removed by filter cloth, and the insoluble impurities are returned to the original liquid tank. The filtered clear liquid with the insoluble impurities removed enters the clear liquid tank for standby, thus obtaining the filter cloth impurity-removed clear liquid.
[0018] Step 3: Ion exchange resin adsorption and impurity removal:
[0019] The concentration of perrhenate ions in the filter cloth impurity removal clear solution obtained in step 2 is detected, the concentration of perrhenate ions in the filter cloth impurity removal clear solution is diluted with deionized water, and the pH of the diluted filter cloth impurity removal clear solution is adjusted with 70 wt.% dilute sulfuric acid, and the perrhenate ions are adsorbed to saturation using ion exchange resin.
[0020] The saturated ion exchange resin is then rinsed with deionized water until it becomes neutral, and ammonia water having a volume 8 to 10 times that of the saturated ion exchange resin is prepared to desorb the saturated ion exchange resin to obtain a desorption solution.
[0021] Step 4: Nanoscale impurity removal of desorption liquid:
[0022] The desorption liquid obtained in step 3 is filtered by cross-flow filtration at room temperature, and the concentrated liquid obtained by cross-flow filtration is returned to the original liquid tank for secondary utilization to obtain a clear liquid obtained by cross-flow filtration.
[0023] Step 5: Concentration of the clear liquid from cross-flow filtration and ultrasound-assisted crystallization:
[0024] The clear liquid obtained by cross-flow filtration in step 4 is used as a material for negative pressure low-temperature evaporation and concentration.
[0025] The temperature of the material is reduced to -3 to -1°C within 8 hours after the cross-flow filtration of the concentrated clear liquid. During the cooling process, an ultrasonic generator with a frequency of 40KHz is used for ultrasonic-assisted crystallization. During the crystallization process, when the material temperature is 5 to 10°C, ammonia water with a volume of 3 to 5% of the material volume and a concentration of 25 to 28 wt.% is added. The crystallization tail liquid is returned to the original liquid tank to obtain crystalline ammonium perrhenate.
[0026] Step 6: Wash and dry the finished product:
[0027] The crystalline ammonium perrhenate obtained in step five is washed with deionized water, and then the washed crystalline ammonium perrhenate is separated by negative pressure filtration, and the filtered crystalline ammonium perrhenate is dried at 120° C. for at least 4 hours to finally obtain an ammonium perrhenate product.
[0028] The present invention also has the following technical features:
[0029] Specifically, in step 1, the elements corresponding to the impurities include one or more of Mo, S, F and Si.
[0030] Specifically, in step 1, the treated impurities are one or more of H2SO4, H2SO3, H2SiF6, H2MoO4 and HF.
[0031] Specifically, the method is used to treat the rhenium element concentration in the crystallization tail liquid at 2 to 5 g / L.
[0032] Preferably, in step 1, the volume of the hydrogen peroxide solution and the volume of the ammonia solution are both 0.5-1% of the volume of the crystallization tail liquid containing impurities to be treated.
[0033] The crystal tail liquid containing the treated impurities is heated to 80-85°C.
[0034] The volume proportion of the quicklime is 0.3-0.5%.
[0035] Preferably, in step 2, the filter element for cross-flow filtration is a titanium filter element.
[0036] Preferably, in step three, the concentration of perrhenate ions in the filter cloth impurity removal clear solution is diluted to 300-800 mg / L.
[0037] The pH of the diluted filter cloth impurity removal clear liquid is adjusted to 5-8.
[0038] The concentration of the ammonia water is 3-5wt.%.
[0039] The ion exchange resin is a chelating resin with a tertiary amine group.
[0040] The adsorption flow rate of the ion exchange resin is 3-5 BV / h.
[0041] The desorption flow rate of the saturated ion exchange resin is 1 to 1.5 BV / h.
[0042] Preferably, in step 4, the filter element specification of the cross-flow filtration is 1 to 10 nm.
[0043] The filter element of the cross-flow filtration is made of titanium.
[0044] Preferably, in step five, the evaporation concentration negative pressure is -0.07 to -0.09 MPa, the material temperature is 65 to 75° C., and the material concentration ratio is ≥12:1.
[0045] Preferably, in step six, the temperature of the deionized water is 0-1°C.
[0046] Compared with the prior art, the present invention has the following technical effects:
[0047] (I) The present invention performs cross-flow membrane filtration on the desorbed liquid after adsorption and desorption by a large-pore weakly alkaline anion chelating resin, thereby effectively reducing the influence of the damaged residue of the ion exchange resin and the enrichment of impurities in the adsorption process of the ion exchange resin on the purity of the ammonium perrhenate product.
[0048] (II) In the present invention, the impurity-containing concentrated solution after filtration and the crystallization tail liquid of the final crystallization process of the product are returned to the original liquid tank, thereby improving the comprehensive recovery and utilization rate of the rhenium element.
[0049] (III) The present invention forms alkaline conditions after supplementing ammonia water, adds quicklime, forms solid precipitation, and utilizes the difference in solubility of calcium salts to achieve the effect of converting soluble impurities in the crystallization tail liquid containing treated impurities into insoluble impurities.
[0050] (IV) The present invention increases the temperature and, while maintaining the high solubility of ammonium perrhenate, uses cross-flow filtration to separate the insoluble impurities in the pre-treated crystallization tail liquid, thereby effectively removing the tiny insoluble impurities in the pre-treated crystallization tail liquid.
[0051] (V) The present invention removes insoluble impurities by solubility change before ion exchange resin adsorption after the temperature drops to room temperature. This operation effectively reduces the influence of some soluble impurities on product purity.
[0052] (VI) The present invention selectively adsorbs perrhenate ions in the filter cloth impurity removal clear liquid by using a large-pore weakly alkaline anion chelating resin. The ion exchange resin used has strong selectivity for perrhenate ions, and the ammonia water used does not introduce external impurities to the ammonium perrhenate product, thereby ensuring the purity of the final ammonium perrhenate product. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The present invention is a flow chart for recovering ammonium perrhenate from the crystallization tail liquid containing impurities that needs to be treated.
[0054] The specific contents of the present invention are further explained in detail below in conjunction with embodiments. DETAILED DESCRIPTION
[0055] It should be noted that the raw materials, instruments, detection methods and processes used in the present invention, unless otherwise specified, all adopt the raw materials, instruments, detection methods and processes known in the prior art. For example, the ultrasonic generator adopts the known ultrasonic generator, the perrhenate ion concentration detection method adopts the known perrhenate ion concentration detection method, and the cross-flow filtration adopts the known cross-flow filtration.
[0056] In the present invention, ammonium perrhenate is also known as ammonium perrhenate, commonly known as ammonium rhenate.
[0057] In the present invention, the raw liquid tank is used to store the crystallization tail liquid containing impurities that needs to be treated.
[0058] In the present invention, room temperature refers to the natural environment temperature during the production process, and usually, the temperature is generally within the range of 20±10°C.
[0059] In the present invention, negative pressure filtration is vacuum filtration.
[0060] The invention is used for treating the crystal tail liquid with high impurity content after the concentrated crystallization of the rhenium recovery system in the flue gas leaching liquid of the molybdenum concentrate roasting.
[0061] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.
[0062] Embodiment 1:
[0063] This embodiment provides a method for recovering ammonium perrhenate from the crystal tail liquid, such as Figure 1 As shown, the method comprises the following steps:
[0064] Step 1: Oxidation and quicklime neutralization pretreatment:
[0065] To 1 m3 of the crystallization tail liquid to be treated containing impurities, 30 wt.% hydrogen peroxide with a volume ratio of 0.5% and 28 wt.% ammonia water with a volume ratio of 0.5% are added in sequence to obtain the crystallization tail liquid containing the treated impurities.
[0066] Table 1 Analysis of the elements in the crystallization tail liquid containing impurities to be treated
[0067] Element composition name Re Mo S F Si content 2.80g / L 2.67g / L 6.16g / L 0.41g / L 55.4mg / L
[0068] In this embodiment, the analysis table of the elements in the crystallization tail liquid containing impurities to be treated is shown in Table 1.
[0069] The crystal tail liquid containing the treated impurities is stirred and heated to 80° C., and then 0.5% quicklime is added to the crystal tail liquid containing the treated impurities according to the volume ratio. After the crystal tail liquid containing the treated impurities is mixed, an insoluble precipitate is formed by utilizing the solubility difference of the calcium salt to obtain the pretreated crystal tail liquid. The chemical reaction of the insoluble precipitate is as follows:
[0070] CaO+H2SO4=CaSO4+H2O
[0071] CaO+H2SO3=CaSO3+H2O
[0072] CaO+H2SiF6=CaSiF2+H2O
[0073] CaO+H2MoO4=CaMoO4+H2O
[0074] CaO+2HF=CaF2+H2O
[0075] Step 2: Nano-scale impurity removal and filter cloth impurity removal:
[0076] Under the condition of 75℃~85℃, the pretreated crystallization tail liquid obtained in step 1 is filtered by cross-flow filtration with a filter element of 100nm. The filter membrane is coated with titanium material, which is resistant to acid and alkali and not easy to introduce impurity elements. The concentrated liquid after filtration is returned to the stock liquid tank for secondary utilization, and the bottom sediment of the stock liquid tank is cleaned regularly.
[0077] After the temperature of the filtered clear liquid drops to room temperature, the insoluble impurities precipitated during the cooling process of the filtered clear liquid are removed through a 120-mesh filter cloth, and the insoluble impurities are returned to the original liquid tank. The filtered clear liquid with the insoluble impurities removed enters the clear liquid tank for standby use, thus obtaining the filter cloth impurity-removed clear liquid.
[0078] Step 3: Ion exchange resin adsorption and impurity removal:
[0079] The concentration of perrhenate ions in the filter cloth impurity removal clear solution obtained in step 2 is detected, and the concentration of perrhenate ions in the filter cloth impurity removal clear solution is diluted to 300 mg / L to 500 mg / L using deionized water, and the pH of the diluted filter cloth impurity removal clear solution is adjusted to 5 to 6 using 70 wt.% dilute sulfuric acid.
[0080] A chelating resin with a tertiary amine group and a pore size of more than 200 nm is used as an ion exchange resin, and perrhenate ions are adsorbed to saturation at an adsorption flow rate of 3 BV / h. The ion exchange resin is adsorbed in series with three resin columns, and one exchange column is filled for every 100 L of ion exchange resin. When the amount of perrhenate ions in the effluent of the first-stage adsorption column is 90% of that in the inlet, it is determined that the ion exchange resin is saturated with the adsorption of perrhenate ions.
[0081] The saturated ion exchange resin was then rinsed with deionized water until it was neutral, and a 3wt.% ammonia solution with a volume 10 times the volume of the saturated ion exchange resin was prepared for desorption of the saturated ion exchange resin at a desorption flow rate of 1 BV / h, and finally a desorption solution was obtained. The element composition analysis table of the desorption solution is shown in Table 2.
[0082] Table 2 Analysis of the elements in the desorption solution
[0083] Element composition name Re Mo S F Si Content of ingredients after impurities removal 2.66g / L 0.53g / L 1.05g / L 0.14g / L 27.7mg / L
[0084] Step 4: Nanoscale impurity removal of desorption liquid:
[0085] The desorption liquid obtained in step three is subjected to cross-flow filtration at room temperature using a 1 nm titanium filter element to remove the damaged residues during the desorption process of the ion exchange resin and the insoluble impurities enriched in the ion exchange resin. The concentrated liquid from the cross-flow filtration is returned to the stock liquid tank for secondary utilization to obtain a clear liquid from the cross-flow filtration.
[0086] Step 5: Concentration of the clear liquid from cross-flow filtration and ultrasound-assisted crystallization:
[0087] The clear liquid obtained by the cross-flow filtration in step 4 is used as the material for negative pressure low-temperature evaporation concentration. The evaporator is a glass rotary evaporator or a glass kettle. The negative pressure of evaporation concentration is -0.07Mpa to -0.09Mpa, the material temperature is 70°C, and the material concentration ratio is 12:1. The low-temperature negative pressure concentration method has a low material evaporation temperature and a high concentration ratio. The material is stable during the concentration process and the loss in the evaporation process is small.
[0088] The temperature of the material is reduced to -3°C to -1°C within 8 hours after the cross-flow filtration of the concentrated clear liquid. During the cooling process, an ultrasonic generator with a frequency of 40KHz is used for ultrasonic-assisted crystallization. When the material temperature is 5°C to 10°C during the crystallization process, ammonia water with a volume of 5% of the material volume and a concentration of 28wt.% is added, and the crystallization tail liquid is returned to the original liquid tank to obtain crystalline ammonium perrhenate. The cavitation principle of ultrasound is used to greatly improve the product particle size and the efficiency of ammonium perrhenate crystallization.
[0089] Step 6: Wash and dry the finished product:
[0090] The crystalline ammonium perrhenate obtained in step 5 is washed with 1°C deionized water to remove soluble ions, and then the washed crystalline ammonium perrhenate is separated by negative pressure filtration, and the filtered crystalline ammonium perrhenate is dried at 120°C for 4 hours to finally obtain an ammonium perrhenate product. By adopting the low-temperature drying method, the moisture content of the final product is less than 0.05%, which improves the drying efficiency and helps to improve the stability and storage life of the product.
[0091] In this embodiment, the mass of the obtained ammonium perrhenate product is 1.85 kg, and the average particle size is 75 μm. The element composition analysis table of the ammonium perrhenate product is shown in Table 3:
[0092] Table 3 Analysis of the elements in ammonium perrhenate products
[0093] Element composition name K S Mo F Si content 35ppm 14ppm 2ppm 15ppm 1.5ppm
[0094] The purity of the obtained ammonium perrhenate product is 99.942%, which is greater than 99.9% and meets the first-class quality standard of the non-ferrous industry (YS / T894-2018).
[0095] Embodiment 2:
[0096] This example provides a method for recovering ammonium perrhenate from a crystallization tail liquid. The method of this example is substantially the same as the method of Example 1, except that:
[0097] In step 1, the addition ratio of hydrogen peroxide and ammonia water is 0.55%; the crystal tail liquid containing the treated impurities is stirred and heated to 85° C.; and the addition amount of quicklime is 0.3%.
[0098] In step 3, the concentration of perrhenate ions is diluted to 450-600 mg / L; the pH of the filter cloth impurity removal clear solution is adjusted to 6-7 after adding dilute sulfuric acid; the concentration of ammonia water added is 4 wt.%; the desorption flow rate is 1.2 BV / h; the element composition analysis of the desorption solution obtained in step 3 is shown in Table 4:
[0099] Table 4 Analysis of the elements in the desorption solution
[0100] Element composition name Re Mo S F Si Content of ingredients after impurities removal 2.56g / L 0.68g / L 0.95g / L 0.16g / L 25.3mg / L
[0101] In step 4, the filter element specification of the cross-flow filtration is 10 nm.
[0102] In step 5, the material temperature is 65°C; the material concentration ratio is 13:1.
[0103] In step six, the temperature of the deionized water is 0°C.
[0104] In this embodiment, the mass of the obtained ammonium perrhenate product is 1.91 kg, and the average particle size is 83 μm. The element composition analysis table of the ammonium perrhenate product is shown in Table 5:
[0105] Table 5 Analysis of the elements in ammonium perrhenate products
[0106] Element composition name K S Mo F Si content 43ppm 21ppm 3.5ppm 18ppm 2.5ppm
[0107] The purity of the obtained ammonium perrhenate product is 99.921%, which is greater than 99.9% and meets the first-class quality standard of the nonferrous industry (YS / T894-2018).
[0108] Embodiment 3:
[0109] This example provides a method for recovering ammonium perrhenate from a crystallization tail liquid. The method of this example is substantially the same as the method of Example 1, except that:
[0110] In step 1, the addition ratio of hydrogen peroxide and ammonia water is 0.6%; the crystal tail liquid containing the treated impurities is stirred and heated to 82°C.
[0111] In step 3, the concentration of perrhenate ions is diluted to 400-450 mg / L; the pH of the filter cloth impurity removal clear solution is adjusted to 6-7.5 after adding dilute sulfuric acid; the concentration of ammonia water added is 4.5wt.%; the desorption flow rate is 1.5BV / h; the element composition analysis of the desorption solution obtained in step 3 is shown in Table 6:
[0112] Table 6 Analysis of the elements in the desorption solution
[0113] Element composition name Re Mo S F Si Content of ingredients after impurities removal 2.78g / L 0.45g / L 1.2g / L 0.06g / L 23.5mg / L
[0114] In step 5, the material concentration ratio is 14:1.
[0115] In step six, the temperature of the deionized water is 0°C.
[0116] In this embodiment, the mass of the obtained ammonium perrhenate product is 1.75 kg, the average particle size is 73.5 μm, and the element composition analysis table of the ammonium perrhenate product is shown in Table 7:
[0117] Table 7 Analysis of the elements in ammonium perrhenate products
[0118] Element composition name K S Mo F Si content 18ppm 8.9ppm 1.5ppm 11ppm 2.3ppm
[0119] The purity of the obtained ammonium perrhenate product is 99.972%, which is greater than 99.9% and meets the first-class quality standard of the nonferrous industry (YS / T894-2018).
Claims
1. A method for recovering ammonium perrhenate from a crystallization tail liquid, characterized in that: The method comprises the following steps: Step 1: Oxidation and quicklime neutralization pretreatment: Adding hydrogen peroxide with a concentration of 25 to 30 wt.% and ammonia water with a concentration of 25 to 28 wt.% in sequence to the crystallization tail liquid containing impurities to be treated, to obtain the crystallization tail liquid containing treated impurities; Stirring the crystallization tail liquid containing the treated impurities and heating it, and then adding quicklime to the crystallization tail liquid containing the treated impurities to obtain a pretreated crystallization tail liquid; Step 2: Nano-scale impurity removal and filter cloth impurity removal: At 75-85° C., the pretreated crystallization tail liquid obtained in step 1 is filtered by cross-flow filtration with a filter element of 100 nm, and the concentrated liquid after filtration is returned to the original liquid tank for secondary utilization; After the temperature of the filtered clear liquid drops to room temperature, the insoluble impurities precipitated during the cooling process of the filtered clear liquid are removed by the filter cloth, and the insoluble impurities are returned to the original liquid tank. The filtered clear liquid with the insoluble impurities removed enters the clear liquid tank for standby use, thus obtaining the filter cloth impurity-removed clear liquid; Step 3: Ion exchange resin adsorption and impurity removal: Detecting the concentration of perrhenate ions in the filter cloth impurity removal clear solution obtained in step 2, diluting the perrhenate ion concentration in the filter cloth impurity removal clear solution with deionized water, adjusting the pH of the diluted filter cloth impurity removal clear solution with 70 wt.% dilute sulfuric acid, and using ion exchange resin to adsorb the perrhenate ions to saturation; The saturated ion exchange resin is then rinsed with deionized water until it becomes neutral, and ammonia water having a volume 8 to 10 times that of the saturated ion exchange resin is prepared to desorb the saturated ion exchange resin to obtain a desorption solution; Step 4: Nanoscale impurity removal of desorption liquid: The desorption liquid obtained in step 3 is filtered by cross-flow filtration at room temperature, and the concentrated liquid of the cross-flow filtration is returned to the stock liquid tank for secondary utilization to obtain a clear liquid of the cross-flow filtration; Step 5: Concentration of the clear liquid from cross-flow filtration and ultrasound-assisted crystallization: The clear liquid obtained by the cross-flow filtration in step 4 is used as a material for negative pressure low-temperature evaporation concentration; The temperature of the material is reduced to -3 to -1°C within 8 hours after the cross-flow filtration of the concentrated clear liquid. During the cooling process, an ultrasonic generator with a frequency of 40KHz is used for ultrasonic assisted crystallization. When the material temperature is 5 to 10°C during the crystallization process, 3 to 5% of the material volume and a concentration of 25 to 28 wt.% of ammonia water are added. The crystallization tail liquid is returned to the stock liquid tank to obtain crystalline ammonium perrhenate. Step 6: Wash and dry the finished product: The crystalline ammonium perrhenate obtained in step five is washed with deionized water, and then the washed crystalline ammonium perrhenate is separated by negative pressure filtration, and the filtered crystalline ammonium perrhenate is dried at 120° C. for at least 4 hours to finally obtain an ammonium perrhenate product.
2. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 1, the elements corresponding to the impurities include one or more of Mo, S, F and Si.
3. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 1, the treated impurities are one or more of H2SO4, H2SO3, H2SiF6, H2MoO4 and HF.
4. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: The method is used to treat the rhenium concentration in the crystal tail liquid of 2 to 5 g / L.
5. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 1, the volume of the hydrogen peroxide solution and the volume of the ammonia solution are both 0.5-1% of the volume of the crystallization tail liquid containing impurities to be treated; The crystal tail liquid containing the treated impurities is heated to 80-85° C.; The volume proportion of the quicklime is 0.3-0.5%.
6. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 2, the filter element of the cross-flow filtration is a titanium filter element.
7. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 3, the concentration of perrhenate ions in the filter cloth impurity removal clear solution is diluted to 300-800 mg / L; The pH of the diluted filter cloth impurity removal clear solution is adjusted to 5-8; The concentration of the aqueous ammonia is 3-5wt.%; The ion exchange resin is a chelating resin with a tertiary amine group; The ion exchange resin adsorption flow rate is 3 to 5 BV / h; The desorption flow rate of the saturated ion exchange resin is 1 to 1.5 BV / h.
8. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 4, the filter element specification of the cross-flow filtration is 1 to 10 nm; The filter element of the cross-flow filtration is made of titanium.
9. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step 5, the evaporation concentration negative pressure is -0.07 to -0.09 MPa, the material temperature is 65 to 75°C, and the material concentration ratio is ≥12:
1.
10. The method for recovering ammonium perrhenate from the crystallization tail liquid according to claim 1, characterized in that: In step six, the temperature of the deionized water is 0-1°C.